Microplastics in surface waters and sediments of the Wei River, in the northwest of China - Ding, Ling; Mao, Ruo fan; Guo, Xuetao; Yang, Xiaomei; Zhang, Qian; Yang, Chen (The Science of the total environment, 2019)
Microplastic pollution is an increasingly important environment problem. Many studies show the occurrence of microplastics in our environmental system. However, the freshwater system is less understood, especially in northwest China. We investigated the occurrence and characteristics of microplastics in the Wei River Basin, which is located in northwestern China. The Wei River is the largest tributary of the Yellow River and runs through three major provinces. In the Wei River, the concentration of microplastics in the surface waters varied from 3.67 to 10.7 items /L and in the sediments, the abundance of microplastics varied from 360 to 1320 items/kg. Fiber (50.1%)was the dominant types in water samples and sediments. The small size (<0.5 mm)(68.1%)were the main size of microplastics in Wei River. The types of microplastics were polyethylene, Polyvinyl chloride and polystyrene, as identified using a Fourier transform infrared spectrometer. This study could be a valuable reference for better understanding the microplastics pollution in inland northwestern China. [Display omitted] •Microplastics were investigated in Wei River in the northwest of China.•The microplastics in the water samples of the Wei River are lower than the microplastics in the sediments.•Fiber and small size (<0.5 mm) were the dominant types and size in water samples and sediments of Wei River.